2015
DOI: 10.17533/udea.rccp.v28n2a01
|View full text |Cite
|
Sign up to set email alerts
|

Dietary organic acids for broiler chickens: a review

Abstract: SummaryThe objective was to summarize and describe the possible mode of action of dietary organic acids and their effects on growth performance of broiler chickens. Previous experiments have suggested that dietary organic acids decrease pH in diets and subsequently reduce pH in the proximal and distal intestine, increase nutrient utilization, and inhibit pathogenic bacterial growth in the gastrointestinal tract (GIT). The degree of pH reduction is usually greater in the upper part of the GIT (crop, proventricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 48 publications
1
48
1
6
Order By: Relevance
“…Kerja BAL ini akan mencegah terjadinya infeksi dan meningkatkan kecernaan pakan dalam saluran pencernaan. Hasil perkembangan BAL akan meningkatkan asam lemak rantai pendek dan asam laktat, menurunkan pH dan mengaktifkan enzim pencernaan, sehingga saluran pencernaan menjadi lebih sehat dan meningkatkan kecernaan protein (Kim et al, 2015).…”
Section: Pendahuluanunclassified
“…Kerja BAL ini akan mencegah terjadinya infeksi dan meningkatkan kecernaan pakan dalam saluran pencernaan. Hasil perkembangan BAL akan meningkatkan asam lemak rantai pendek dan asam laktat, menurunkan pH dan mengaktifkan enzim pencernaan, sehingga saluran pencernaan menjadi lebih sehat dan meningkatkan kecernaan protein (Kim et al, 2015).…”
Section: Pendahuluanunclassified
“…Butyric acid (C 4 H 8 O 2 ) is the most important source of energy to the epithelial cells; it required for normal epithelial cell development and has antibacterial activity in the gastrointestinal tract [15]. Many poultry researchers intensively studied butyric acid; diets supplemented with butyric acid improved feed efficiency and BW gain of broilers [16].…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in pH could also be achieved by adding formic acid to diets. As reviewed by Kim et al [10], supplementation of formic acid was reported to affect the microbial community and lead to increased performance and nutrient digestibility in broiler chickens. Likely, the addition of formic acid to CaCO 3containing diets and the use of Ca-formate in uences the microbial community in the digestive tract, possibly through changes in digesta pH [11,12].…”
Section: Introductionmentioning
confidence: 99%